2013
DOI: 10.1530/erc-12-0399
|View full text |Cite
|
Sign up to set email alerts
|

A founder SDHB mutation in Portuguese paraganglioma patients

Abstract: We would like to report a genetic screening of SDHB, SDHC, SDHD and SDHAF2 genes (hereafter abbreviated to SDHx) in patients with paragangliomas (PGL) and phaeochromocytomas (PCC) from northern Portugal.PGL and PCC are neuroendocrine tumours that can be caused by heterozygous germline loss-of-function mutations in SDHx genes (Gimenez-Roqueplo et al.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 9 publications
1
5
0
1
Order By: Relevance
“…8,10,11,58,59 Loss of SDHB protein expression is seen in pheochromocytomas/paragangliomas either harboring a mutation in any of the SDH genes or with somatic hypermethylation of the SDHC promoter region, 42 whereas loss of both SDHB and SDHA immunoreactivity is demonstrated only in the context of an SDHA mutation. [8][9][10][11][12][13][14][15][16][17][18][19][20] In agreement with previous studies, 8,10,11,[17][18][19][20] SDHB-/C-/D-and SDHAmutated tumors displayed the aforementioned and NF1 mutations, 8,10 respectively. By using a mouse monoclonal (21A11) SDHB antibody at a low concentration (1 in 1000), Gill et al 10 suggested that VHL-associated tumors could be classified as negative or weak diffuse rather than positive as demonstrated by a high concentration approach of two SDHB antibodies.…”
Section: Discussionsupporting
confidence: 91%
“…8,10,11,58,59 Loss of SDHB protein expression is seen in pheochromocytomas/paragangliomas either harboring a mutation in any of the SDH genes or with somatic hypermethylation of the SDHC promoter region, 42 whereas loss of both SDHB and SDHA immunoreactivity is demonstrated only in the context of an SDHA mutation. [8][9][10][11][12][13][14][15][16][17][18][19][20] In agreement with previous studies, 8,10,11,[17][18][19][20] SDHB-/C-/D-and SDHAmutated tumors displayed the aforementioned and NF1 mutations, 8,10 respectively. By using a mouse monoclonal (21A11) SDHB antibody at a low concentration (1 in 1000), Gill et al 10 suggested that VHL-associated tumors could be classified as negative or weak diffuse rather than positive as demonstrated by a high concentration approach of two SDHB antibodies.…”
Section: Discussionsupporting
confidence: 91%
“…For instance, in VHL disease-associated pheochromocytoma, codon 167 of VHL gene appears as a first target, since missense mutations in this codon are strongly associated with pheochromocytoma development [60]. In addition, we should be aware of founder mutations already reported for SDHx genes in different countries such as the Netherlands, Poland, Italy, Spain, and Portugal in order to develop effective screening protocols [158162]. …”
Section: Genetic Testing Strategy In Paraganglioma/pheochromocytomamentioning
confidence: 99%
“…Portugal has a relatively homogeneous population and several founder mutations or mutations with a founder effect have been described associated with cancer predisposition [28][29][30][31][32][33]. Our group has recently reported that the BRCA2 c.156_157insAlu rearrangement, a Portuguese founder mutation, and the BRCA1 c.3331_3334del mutation, which shows a founder effect in Portugal, represent 33.6 and 12.6 %, respectively, of HBOC families with pathogenic mutations, accounting for 57.1 % of BRCA2 and 30.6 % of BRCA1 deleterious mutations [33].…”
Section: Introductionmentioning
confidence: 99%